The yield of chromosomal microarray analysis among pregnancies terminated due to fetal malformations. (17th January 2022) - Pasternak, Yael; Daykan, Yair; Tenne, Tamar; Reinstein, Eyal; Miller, Netanella; Shechter-Maor, Gil; Maya, Idit; Biron-Shental, Tal; Sukenik Halevy, Rivka
Abstract: Background: Chromosomal microarray analysis (CMA) is preferred for genetic work-up when fetal malformations are detected prenatally. Objectives: To assess the detection rate of CMA after pregnancy termination due to abnormal ultrasound findings. Methods: CMA was successfully performed in 71 pregnancies using fetal DNA (mainly from skin) or placenta. Data regarding clinical background, pregnancy work-up, and CMA were analyzed. Results: Findings were abnormal in 17 cases (23.9%), of which 13 were detectable by karyotype. The incremental yield of CMA was 4/71 (5.6%); 1/32 (3.1%) for cases with an isolated anomaly and 3/39 (7.7%) for cases with nonisolated anomalies. Conclusions: CMA yield from terminated pregnancies was 23.9%. Although most chromosomal abnormalities are detectable by karyotype, CMA does not require viable dividing cells; hence, it is more practical for work-up after termination. In most cases, the diagnosis was followed by consultation regarding the risk of recurrence and recommendations for testing in subsequent pregnancies.